Peningkatan Nilai Tambah (Value Added) Produksi Minyak Goreng Kelapa Tradisional - Dody Radiansah; Revi Sesario; Adi Marjani Patappa; Ichsan Ichsan; Th. Candra Wasis; Nur Fajar Febtysiana; Janne Hillary (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2023)
This Community Service activity involved farmer groups and the Family Welfare Development Organization (PKK) in Sungai Rasau Village. There is plenty of potential for the production of coconut plantations in the village, but the business of differentiating coconut into cooking oil is of little interest to the community. Low interest is due to relatively limited knowledge and understanding of the economic potential of cooking oil products, especially market uptake. Efforts can be made to increase the added value of cooking oil products. This program aimed to increase the added value of cooking oil products to improve market uptake. Accordingly, the direct learning method was used in this service program, and its activities included training and mentoring. The results of the service program showed that the program that had been implemented generated new enthusiasm for Farmer Groups and PKK. Also, the trademark “MIKOM” was used as branding for coconut cooking oil products from Sungai Rasau Village, accompanied by an attractive offer sentence as a form of online promotion of traditional coconut cooking oil products. Differences in methods and production costs incurred as well as adjustments to the latest costs due to the increase in fuel, became an obstacle for training participants to calculate product selling prices. The participants poorly understood the information technology training because the village lacked sufficient Internet access. Farmer groups carried out the marketing simulation for coconut cooking oil as producers of coconut cooking oil, while the PKK acted as marketing field coordinator.